2010
DOI: 10.1039/b917668c
|View full text |Cite
|
Sign up to set email alerts
|

Integration and detection of biochemical assays in digital microfluidic LOC devices

Abstract: The ambition of lab-on-a-chip (LOC) systems to achieve chip-level integration of a complete analytical process capable of performing a complex set of biomedical protocols is hindered by the absence of standard fluidic components able to be assembled. As a result, most microfluidic platforms built to date are highly specialized and designed to fulfill the requirements of a single particular application within a limited set of operations. Electrowetting-on-dielectric (EWOD) digital microfluidic technology has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
159
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 108 publications
0
159
0
1
Order By: Relevance
“…We believe that the developed technology proposed herein provides a highly flexible tool for the rapid analysis of biomolecular interactions under numerous different conditions. Work is underway to integrate these devices with label-free detection systems [2] and various biological species (DNA, RNA, proteins, cells, etc.). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the developed technology proposed herein provides a highly flexible tool for the rapid analysis of biomolecular interactions under numerous different conditions. Work is underway to integrate these devices with label-free detection systems [2] and various biological species (DNA, RNA, proteins, cells, etc.). …”
Section: Resultsmentioning
confidence: 99%
“…Among the various types of microfluidic devices developed in the past years, digital microfluidics (DMF) has emerged as a promising technology that offers key advantages to perform miniaturized bioassays [2][3][4]. In DMF devices, nl-size liquid droplets are manipulated at will on a 2D surface using electrowetting-ondielectric (EWOD) forces applied with an array of computer-controlled electrodes (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional heterogeneity of monoclonal human colon cancer (Dalerba et al, 2011) and circulating tumor cells (Powell et al, 2012) were revealed by commercially available qRT-PCR equipment in microfluidic platform. Another common approach involves a series of components which integrate various steps in metering, formulation, mixing, analysis, and storage (Malic et al, 2010;Mark et al, 2010). One module which arises repeatedly in high-throughput analysis is storage.…”
Section: Uses Of Microfludics In Real Time Qrt-pcrmentioning
confidence: 99%
“…16 Reliability and robustness are still great challenges of DMFbased micro-reactors [9][10][11][12][13][14] due to the co-existence of different sorts of chemical reagents and biological species. It is particularly true for those containing sticky constituents, and the various irregular sample-originated surface damages, adsorption, and aging effects 17 of the insulation and hydrophobic materials of the DMF chip. For instance, in a sequential reaction, a droplet sample may fail to reach the expected destination due to a premature charging time, halting the entire system.…”
Section: Introductionmentioning
confidence: 99%